Cellular automata model for emergent properties of pressure flow in single nephron compliance tubule - Reddy Kesu, Siva Manohar; Ramasangu, Hariharan (Institute of Advanced Engineering and Science, 2022)
Numerical analysis plays a vital role in the computational modeling of a nephron. The solutions from numerical methods exhibit regular, period doubling, and irregular oscillations as global behavior. A single nephron compliance tubular model with transport mechanism and autoregulatory mechanism has been developed using the cellular automata framework in this paper. Global emergent behavior of the biological system has been captured using cellular automata framework. An ultradiscretization technique is used to convert the governing partial differential equations of a single nephron compliance tubular model to cellular automata local rules. The global emergent behaviors from the local cellular automata rules have been compared with the reported experimental analysis. The cellular automata framework in biological modeling is an emerging perspective to model global functional behaviors.